Serum 25‐hydroxyvitamin D and left ventricular systolic function in a non‐smoking population: the Tromsø Study. (May 2013) - Kamycheva, Elena; Wilsgaard, Tom; Schirmer, Henrik; Jorde, Rolf
<x xml:space="preserve">Abstract</x> Aims The myocardium is considered to be an important target organ for parathyroid hormone and 1, 25‐dihydroxyvitamin D, the active metabolite of vitamin D. Vitamin D inadequacy has also been linked to cardiovascular morbidity. We aimed to evaluate the relationship between serum 25‐hydroxyvitamin D [25(OH)D] and LV systolic function in a general population. Methods and results In the fourth Tromsø Study, M‐mode echocardiography was performed in 2504 subjects with available serum 25(OH)D measurements. Measurements of EF and LV mass indexed by height (LVMH) were obtained. Only non‐smoking men (n = 790) and women (n = 944) were included in the final analysis. Linear regression was used to assess the association between serum 25(OH)D and measurements of systolic function, and logistic regression was applied to assess the effect of serum 25(OH)D on the lowest quartile of EF (yes/no) and LV hypertrophy (LVH) (yes/no). We found no significant associations between vitamin D concentrations and measures of LV systolic function, when adjusted for other risk factors and the season when 25(OH)D sampling was performed [β –0.03, 95% confidence interval (CI) –0.08 to 0.03, and β –0.01, 95% CI –0.07 to 0.06 for LVMH and EF in men; and β 0.02, 95% CI –0.03 to 0.07, and β 0.01, 95% CI –0.05 to 0.07 for LVMH and EF in women]. Serum 25(OH)D did not predict EF and/or LVH in both genders. Conclusions In our population‐based study, increased serum 25(OH)D was not associated with better LV systolic function, when adjusted for other risk factors and for season of vitamin D sampling.